Implementation of the Linear Regression Method to Determine Predictions of the Influence of Religion on General Election Participation - fitria, Saniya Izza; Senja Fitrani, Arif; Eviyanti , Ade (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2024)
This research aims to predict election participation in places of worship through statistical data analysis methods and predictive algorithms. Election participation, as a complex phenomenon, is influenced by various factors, with religion often being a crucial element that motivates or inhibits voter turnout. This study uses variables from Central Statistics Agency (BPS) data and recapitulation of previous general elections, based on historical patterns. Using a statistical approach, the relationship between religious variables and the level of voter participation in places of worship is identified. The linear regression method is used to predict the influence of religion on election participation. In this research, a series of scenarios were carried out, and the research results showed different variations in R-squared (R-Square) and Mean Squared Error (MSE) results. The best scenario, namely the R-squared scenario with a value of around 0.00012 and an MSE of 0.09934, highlights the potential relationship between religion and voter participation. These findings suggest the need for further considerations in this context, as well as demonstrating the need for model adjustments to improve the accuracy of future election predictions.